2022
DOI: 10.3389/fmolb.2022.801309
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid, Highly Sensitive and Open-Access SARS-CoV-2 Detection Assay for Laboratory and Home Testing

Abstract: RT-qPCR-based diagnostic tests play important roles in combating virus-caused pandemics such as Covid-19. However, their dependence on sophisticated equipment and the associated costs often limits their widespread use. Loop-mediated isothermal amplification after reverse transcription (RT-LAMP) is an alternative nucleic acid detection method that overcomes these limitations. Here, we present a rapid, robust, and sensitive RT-LAMP-based SARS-CoV-2 detection assay. Our 40-min procedure bypasses the RNA isolation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…The high acceptability of self-collected gargle as reported by some studies suggested that it may also potentially help to abate the testing hesitancy that is not uncommonly encountered in mandatory testing scenarios [ 35 , 47 , 77 ]. Our findings provide an evidence-based justification for COVID-19 testing approaches in national and international guidelines, and support the recommendation of gargling as an inexpensive and easy sampling approach for routine repeated testing in various community settings [ 78 ], including primary and secondary schools, universities [ 77 , 79 , 80 ], nursing homes [ 81 ], daycare facilities for children aged 1–7 years [ 67 ], children's hospitals [ 82 ], homes [ 83 ] and in other specific high-risk populations having medically indicated needs for repeated testing [ 78 ].…”
Section: Discussionmentioning
confidence: 66%
“…The high acceptability of self-collected gargle as reported by some studies suggested that it may also potentially help to abate the testing hesitancy that is not uncommonly encountered in mandatory testing scenarios [ 35 , 47 , 77 ]. Our findings provide an evidence-based justification for COVID-19 testing approaches in national and international guidelines, and support the recommendation of gargling as an inexpensive and easy sampling approach for routine repeated testing in various community settings [ 78 ], including primary and secondary schools, universities [ 77 , 79 , 80 ], nursing homes [ 81 ], daycare facilities for children aged 1–7 years [ 67 ], children's hospitals [ 82 ], homes [ 83 ] and in other specific high-risk populations having medically indicated needs for repeated testing [ 78 ].…”
Section: Discussionmentioning
confidence: 66%
“…For the implementation of the RT-LAMP assay we used NEB enzymes and a colorimetric-based readout, however, royalty-free self-purified Bst-LF polymerase and the HIV-RT have been also reported to work very well for RT-LAMP for SARS-CoV-2 (23). Using self-produced Bst-LF polymerase and HIV-RT preparations we found that slight modifications of the sample analysis procedures (using a fluorescent readout, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In RT-LAMP, this can be replaced by using fluorescence dyes to detect the produced DNA, or dyes to detect a chemical change associated with a successful amplification, e.g. a pH drop (22) or the formation of a magnesium pyrophosphate precipitate (23). In addition, since fluorescence and color readout can constitute bottlenecks, we and others developed DNA barcoding strategies to permit pooled analysis of many samples using next-generation sequencing (termed LAMP-sequencing) (24)(25)(26), providing the possibility of a massively scaled up sample throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively easy to implement; however, this strategy requires a heating source and optimization of the heating conditions. [10,13,23,[29][30][31][32][33][34]37,40,41] Nasopharyngeal swabs RT-PCR Thermal shock of the sample at 95 • C for 5 min followed by 4 • C for 10 min.…”
Section: Sample Type Naat/detection Methods Sample Preparation Strategymentioning
confidence: 99%